2020
DOI: 10.1029/2020gc009389
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of Natural Magnetite Ensembles: Micromagnetics of Silicate‐Hosted Magnetite Inclusions Based on Focused‐Ion‐Beam Nanotomography

Abstract: A fundamental task in rock magnetism is to identify the magnetic domain states adopted by natural remanence carriers because these control the remanence acquisition process, the stability of the remanent magnetization over geological time, and subsequently the reliability of the stored paleomagnetic information. Most rocks contain a mixture of magnetic minerals covering a broad range of particle sizes and shapes. Rock magnetism broadly classifies these particles into superparamagnetic (SP), stable single-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 60 publications
2
55
1
Order By: Relevance
“…The second hypothesis implies that the magnetite and the accompanying phases precipitated from an Fe-bearing plagioclase, which became supersaturated with respect to magnetite (Wenk et al 2011;Biedermann et al 2016;Nikolaisen et al 2020). In this case, the magnetite and the accompanying phases were in contact with the crystal structure of the host plagioclase during their entire nucleation and growth history.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis implies that the magnetite and the accompanying phases precipitated from an Fe-bearing plagioclase, which became supersaturated with respect to magnetite (Wenk et al 2011;Biedermann et al 2016;Nikolaisen et al 2020). In this case, the magnetite and the accompanying phases were in contact with the crystal structure of the host plagioclase during their entire nucleation and growth history.…”
Section: Discussionmentioning
confidence: 99%
“…We here apply the general "slice-and-view" method for extracting data, processing the resulting image stack, and calculating micromagnetic models as it is described step-bystep in Nikolaisen et al [2020]. For this study only few modifications to the method were introduced to increase the quality and accuracy of the results.…”
Section: Methodsmentioning
confidence: 99%
“…Below only these changes are explained in sufficient detail to allow replication. All other details are described in Nikolaisen et al [2020].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…netite and titanomagnetite) within silicates are widely distributed in marine sediments, and their size ranges from a few nanometers to several micrometers with variable morphologies (Chang, Bolton, et al, 2016;Hong et al, 2019;Hounslow, 1996;Hounslow & Morton, 2004;Nikolaisen et al, 2020;Usui et al, 2018;Zhang et al, 2018). It is suggested that they have stable single domain (SD)like magnetic properties and can be preserved in perturbed environments due to the protection of silicate (Chang, Bolton, et al, 2016;Chang et al, 2021), thus recording a reliable paleomagnetic and paleoenvironmental information.…”
mentioning
confidence: 99%